Literatur Review: D-Allulose 3-Epimerase from Microbial Sources and its Potential Uses - Az-Zahra, Fauziah; Putri, Dwi Hilda; Irdawati, Irdawati; Handayani, Dezi (Jurnal Biologi Tropis, 2025)
D-allulose, or psicose, is a rare, low-calorie sugar with various health benefits, such as managing blood sugar levels and lowering the risk of obesity, making it an ideal alternative to sucrose. In the food and pharmaceutical sectors, this study aims to review the characteristics and potential of D-allulose 3-epimerase (DAEase) enzymes from different microbial sources, along with the challenges and prospects associated with industrial-scale applications. The methodology involved a literature review to analyse the properties of DAEase enzymes, including specific activity, thermal stability, and optimal temperature and pH conditions from different microbial producers. The results showed that the enzyme from Agrobacterium sp. exhibited the highest specific activity, while the enzyme from Labedella endophytica offered the best thermal stability. In conclusion, DAEase enzymes show significant potential in the production of D-allulose, especially in supporting the global trend towards healthier and more environmentally friendly low-calorie food products. Further research is recommended to focus on improving production efficiency and technology development for large-scale commercial applications.